Improving Speaking Skill of the Tenth Grade Students of SMA Negeri 1 Palu Through Comic Strip - Winda Ananda Putri Mustaqim; Abd. Kamarrudin; Afrillia Anggraeni; Anjar Kusuma Dewi (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
The objective of this research is to find out if whether Comic strip is effective improve the students' speaking skills or not. This research explores whether using comic strips can effectively improve students' speaking skills by making learning more engaging and reducing their anxiety about speaking in English. The researcher applied a pre-experimental research design which involved only one class. The population of this research was the tenth-grade students at SMA Negeri 1 Palu. The researcher selected the sample by using a purposive sampling technique. The sample of this research was the students of X E7 consisting of 36 students. The technique of data collection used instrument tests (pre-test and post-test). The experimental class was treated by applying the Comic Strip. The result of the data analysis shows that there was a significant difference between the pre-test and post-test. The researcher found that the t-counted (3.33) was higher than the t-table (2.021). It means that the hypothesis was accepted. In conclusion, Comic Strip effective to improve the speaking skills of the tenth-grade students of SMA Negeri 1 Palu.